A new species of the genus Aleuroparadoxus (Hemiptera: Aleyrodidae) from Oaxaca, Mexico - Sánchez-Flores, Oscar Ángel; Carapia-Ruiz, Vicente Emilio; Castillo-Gutiérrez, Antonio (Instituto de Ecología, A.C., 2022)
A new species of whitefly is described, Aleuroparadoxus oaxacensis Carapia-Ruiz & Sánchez-Flores sp. nov., based on specimens collected on the upper side of leaves of Guaiacum coulteri A. Gray (Zygophyllacea) in Huatulco, Oaxaca, Mexico. This species does not present tubercles on the inner margin of the caudal ridges and the anterior and posterior halves of the pupa are of similar width and is included in the sapotae group as it presents dark brown color and semioval to semicircular form. Microphotographs of pupal morphological structures are provided and separation from similar species is briefly discussed. Also, a key to the Mexican species of Aleuroparadoxus is provided.